MEMAHAMI PERILAKU STAKEHOLDERS INDONESIA DALAM ADOPSI IFRS: TINJAUAN ASPEK KEPENTINGAN, BAHASA, DAN BUDAYA - Efferin, Sujoko; Rudiawarni, Felizia Arni (Jurnal Akuntansi dan Keuangan Indonesia, 2014)
This study examines the dynamics of the implementation of IFRS in Indonesia and challenges faced by its stakeholders by using interpretive-qualitative research paradigm. In-depth interviews, observations, and documentary analysis were used during data collection processes. The results were then cross-examined through triangulation. More specifically, this study attempts to identify problems arised during the implementation and the responses of the stakeholders. The authors hope that the findings can enrich the literatures about the interconnectedness among accounting, culture, language, and stakeholders’ interests in the context of developing countries, especially Indonesia. Our results indicate that there is an interdependence among the stakeholders (regulator, auditor, user, preparer, and higher education institutions) in which there is no party that can individually ensure the successfulness of the IFRS implementation. Synergistic, long-term oriented collective efforts among those parties are required since they all have internal constraints that can inhibit the implementation. In addition, culture (including language) exacerbates the problems and, hence, require long-term, strategic responses in macro level. Finally, this study suggests seven propositions conditioning the effectiveness of IFRS implementation in a national context.